Landscape character for tourism route planning: A case study of the Kuala Selangor – Sabak Bernam route - Zakariya, Khalilah; Abdul Wahab, Nur Amirah; Tukiman, Izawati; Che Haron, Roziha (School of Tourism, Hospitality & Event Management, Universiti Utara Malaysia, 2017)
Tourism is the act of travel for the purposes of leisure, pleasure or business, and the provision of services for this act. There are two important components that make up tourism which are practice of travelling for pleasure recreation and the business of providing tours and services for persons travelling. While tourism routes promise to bring together a variety of activities and attractions under a unified theme, the routes can also stimulate entrepreneurial opportunity through the development of ancillary products and services. There are strategies for the tourism route planning that could increase tourism development opportunities, where the planning of resources and attractions can be better integrated to support infrastructural development of a region, conservation and rejuvenation of cultural and natural resources. This paper examined the significant characters of the rural tourism route planning along the Kuala Selangor to Sabak Bernam rural routes. Based on 250 survey questionnaires among locals and tourists, this study evaluated the importance of nine criteria of rural tourism attraction, which are rural culture, recreation activities, traditional built environments, agriculture, nature and landscape features, history and heritage, sensory and experience, accessibility and infrastructure. The findings suggest that the intangible criteria are pertinent to support the tangible criteria found along the rural route. This paper concludes by recommending ways to improve the rural tourism route by identifying and conserving certain attributes in the rural landscape characters that are valuable for a tourism route.